2003
DOI: 10.1002/joc.972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three infrared satellite techniques to estimate accumulated rainfall over the Iberian Peninsula

Abstract: The potential of three infrared satellite-based techniques to estimate accumulated rainfall is tested, and the techniques are compared and contrasted. The tests are conducted in the western Mediterranean area and for the first time in the Iberian Peninsula. The well-known Arkin and the Negri-Adler-Wesley techniques are applied, as well as the Autoestimator technique during the autumn of 1994. Because the aim of this work is to automate the process of extracting the data inferred in a large number of satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…T10 and T50 are the warmest temperatures of the coldest 10% and 50% of the pixels respectively. Attempts are made to adjust rain rates for mid-latitude [30]- [32]. It is found that the rain rates recalibration allows a better description of non-tropical events.…”
Section: Naw Approachmentioning
confidence: 99%
“…T10 and T50 are the warmest temperatures of the coldest 10% and 50% of the pixels respectively. Attempts are made to adjust rain rates for mid-latitude [30]- [32]. It is found that the rain rates recalibration allows a better description of non-tropical events.…”
Section: Naw Approachmentioning
confidence: 99%
“…The most techniques are mainly applied to tropical regions where rainfall is largely provided by convective cells. IR satellite techniques were used in the western Mediterranean region in various conditions and with variety of aims [9]. The south shore of the Mediterranean sea presents a complex climate.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested to use optical and microphysical parameters to estimate the precipitations in this case [10]- [11]. In the recent past, Tarruella and Joge have shown that we can adapt the Arkin (GPI) and NAW (Negri Adler Wesley) techniques for estimating rainfall in the Mediterranean region [9]. The question is: can we adapt the GPI method to the south shore of the Mediterranean Sea?…”
Section: Introductionmentioning
confidence: 99%